The economic impact of fintech adaptation on sustainable banking performance: The role of green finance and innovation in Indonesia - Rizwana, Zahra Ardya; Adillah, Meylia; Anggrayni, Vidiyana; Rosalia, Tita; Alfandito, Muhammad Zidane; Purwanto, Edi (Journal of Economics Research and Policy Studies, 2025)
This study examines the economic impact of fintech adaptation on sustainability performance in the Indonesian banking sector, with green finance and green innovation as mediating variables. A quantitative research approach was employed, utilizing secondary data from six Indonesian banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Path analysis was applied to evaluate to assess relationships among fintech adaptation, green finance, green innovation, and sustainability performance. The findings reveal that fintech adaptation significantly influences green finance but has a limited impact on green innovation and direct sustainability performance. Additionally, green finance and green innovation do not significantly mediate the relationship between fintech adaptation and sustainability performance. These results highlight the challenges of integrating fintech into sustainable banking initiatives in emerging markets. The study underscores the need for enhanced regulatory frameworks, strategic fintech adoption, and increased collaboration among financial institutions to drive sustainability efforts. Future research should explore additional factors influencing sustainability performance in banking.